2010
DOI: 10.1002/jbm.b.31648
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of viability and proliferation of alginate‐poly‐L‐lysine–alginate encapsulated myoblasts using flow cytometry

Abstract: Genetically modified cells encapsulated in alginate-poly-L-lysine-alginate (APA) are being developed to deliver therapeutic products to treat a variety of diseases. The characterization of the encapsulated cells thus becomes paramount. This study reports a novel method to assess the viability, granularity and proliferation of encapsulated cells based on flow cytometry. The in vitro viability of encapsulated G8 murine myoblasts secreting canine FVIII (cFVIII) measured by flow cytometry was comparable to the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Almost all the encapsulated cells (93-98%) were viable after encapsulation, which was similar to the other groups ( Figure 3A). The results were consistent with previous studies (Maguire et al, 2006;Thakur et al, 2010). There were no significant differences among all groups during the progressive stages of apoptosis ( Figure 3B and C).…”
Section: The Effect Of the Encapsulation Process On Cell Apoptosissupporting
confidence: 83%
See 2 more Smart Citations
“…Almost all the encapsulated cells (93-98%) were viable after encapsulation, which was similar to the other groups ( Figure 3A). The results were consistent with previous studies (Maguire et al, 2006;Thakur et al, 2010). There were no significant differences among all groups during the progressive stages of apoptosis ( Figure 3B and C).…”
Section: The Effect Of the Encapsulation Process On Cell Apoptosissupporting
confidence: 83%
“…In combination with the annexin V assay, our results indicated that stimuli from encapsulation process did not destroy ER homeostasis. Moreover, not only tumour cells but also normal cells (Thakur et al, 2010), even stem cells (Maguire et al, 2006), maintained viability when cultured within microencapsulate by electrostatic droplet technology. Overall, encapsulation process might be universal and friendly to the mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method of analysis defines dead cells as those which have a compromised cell membrane. An apoptotic/ necrotic dead cell with a compromised cell membrane is measured by the loss calcein intracellular staining and the change in its size and granularity, while (Bertho et al 2000;Thakur et al 2010). This is inherently more sensitive than relying on the ability of a second dye such as 7-AAD or ethidium bromide to label cells with a damaged cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…[27] The most widely studied alginate-based formulations involve complexation with polycations, poly-L-lysine and chitosan in particular, to control permeability and increase strength and stability. [28][29][30] Nevertheless, other, different alginate-based formulations have been examined over the years to further improve the effectiveness of cell encapsulation, including cross-linked alginate-gelatine, [31] alginate-poly(ethylene glycol), [32] or alginate and hyaluronic acid stabilized with polyethyleneimine. [33] Together with alginate, different biopolymers capable of gelling under mild conditions have attracted attention as cell carriers.…”
Section: Introductionmentioning
confidence: 98%